2016
DOI: 10.1111/ele.12708
|View full text |Cite
|
Sign up to set email alerts
|

What's your move? Movement as a link between personality and spatial dynamics in animal populations

Abstract: Recent studies have established the ecological and evolutionary importance of animal personalities. Individual differences in movement and space-use, fundamental to many personality traits (e.g. activity, boldness and exploratory behaviour) have been documented across many species and contexts, for instance personality-dependent dispersal syndromes. Yet, insights from the concurrently developing movement ecology paradigm are rarely considered and recent evidence for other personality-dependent movements and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
346
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 332 publications
(361 citation statements)
references
References 83 publications
(301 reference statements)
13
346
2
Order By: Relevance
“…Our results showed that it is important to let individuality emerge when making population-level inferences. Recent studies targeting different species and ecological contexts are increasingly paying more attention on the importance of considering inter-individual variability as a key component of a population rather than noise in the analyses [9, 25, 5558]. Large variation in the learning process may be due to variation in the factors affecting the animal when and how learning occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that it is important to let individuality emerge when making population-level inferences. Recent studies targeting different species and ecological contexts are increasingly paying more attention on the importance of considering inter-individual variability as a key component of a population rather than noise in the analyses [9, 25, 5558]. Large variation in the learning process may be due to variation in the factors affecting the animal when and how learning occurs.…”
Section: Discussionmentioning
confidence: 99%
“…e ., random slope for age and random intercept for individual, thus allowing animals of different age to learn differently). Further investigations should identify personality traits from spatial behaviour [55], and then disentangle how learning specifically varies as a function of personality types. There is an urgent need to deepen our understanding of the relation between inter-individual variability in behaviour in the wild to personality traits [58] to better tackle variation in the responses by wildlife to human activity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, bolder barnacle geese produce more information, whereas shy individuals use this information more than others [47]. Thus, the density or spatial distribution of particularly informative individuals could have a disproportionate effect on population demographics [48,49], a concept we revisit in the section on community dynamics. Clearly, this kind of positive feedback has the potential to interact with negative density dependence in complex ways.…”
Section: How and When Does Social Information Use Affect Population Dmentioning
confidence: 99%
“…However, the first and fastest way to cope with a novel situation is often an individual behavioural response that ultimately depends on the behavioural plasticity that has evolved under past conditions (Sih et al., ; Wong & Candolin, ). Plasticity in spatial behaviour is particularly important because spatial dynamics determine the interaction with conspecifics, with other species and with the surrounding abiotic environment (Clobert, Galliard, Cote, Meylan, & Massot, ; Spiegel, Leu, Bull, & Sih, ). Accordingly, interindividual differences in movement ecology, and the range of spatial plasticity, likely play an important role in determining the ecological and evolutionary dynamics of populations (e.g., Harrison et al., ; Villegas‐Ríos, Réale, Freitas, Moland, & Olsen, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, bolder or more aggressive individuals tend to be more exploratory and disperse further (Cote, Clobert, Brodin, Fogarty, & Sih, ). Yet, empirical evidence of personality‐dependent spatial behaviour for traits other than dispersal is still scarce (Spiegel, Leu, Sih, Godfrey, & Bull, ; Spiegel et al., ). Personalities may also explain the differences in plasticity observed between individuals in response to changes in their social environment (Aplin et al., ) and population dynamics (Cote & Clobert, ).…”
Section: Introductionmentioning
confidence: 99%